The Scientific Comparison between Web-Based Site and Web-Builder (Open Source) Project: Functionalities, Usability, Design and Security (International Journal of Scientific Research and Management (IJSRM), 2018)
In developing web sites there are some rules that developers should depend on in order to create a site suitable to the users’ needs and also to make them as comfort as possible when they surf it. Before creating any website or operating any application, it is important for developers to address the functionality, design, usability and security of the work according to the demands. Every developer has his/her own way to develop a website, some prefer to use website builders and while others prefer to what they have primarily formed in their mind What they have primarily formed in their mind preferred software and programming languages. Therefore, this paper will compare the web based sites and open source projects in terms of functionality, usability, design and security in order to help academic staffs or business organization for choosing the best way for developing an academic or e-commerce web site.